Problems of international development taxes: Illustrated by the financing system for science and technology for development - Joachim Betz (Intereconomics, 1982)
Attempts by the developing countries to replace the largely voluntary provision of development aid by a system that would free official resource flows from the possibility of political interference by the donors and from the need for yearly budgetary allocations have been going on for some time. The present author here examines the proposal of the Group of 77 for a Financing System for Science and Technology for Development.
Keywords: 330; International Taxation